We know that we are all together: a case study of the communal coping process in a professional ice hockey team - Mahot, K.; Pété, E.; Lienhart, N.; Doron, J. (The Sport Psychologist, 2025)
On the road to success, team members combine efforts to cope with stressful situations they face together. This case study explores communal coping in a professional ice hockey team during the COVID-19 crisis, involving 20 male players (Mage = 28.5). Using template thematic analysis of semistructured interviews, three shared stressors were identified: the suspension of competitions, uncertainty about logistics and career stability, and the loss of social opportunities. These stressors affected psychological well-being, interpersonal relationships, and team performance. Findings reveal various communal coping strategies including problem-focused efforts (e.g., effort expenditure), relationship-focused coping (e.g., team days), and communal emotional management (e.g., compassionate conversations). Leaders contribute to the communal coping process by fostering a positive social environment and initiating coping strategies. By introducing the concept of transactional space, this study highlights the importance of communication and group dynamics in coordinating efforts against adversity and suggests that training leaders could enhance team resilience.